2010
DOI: 10.1021/ac9025169
|View full text |Cite
|
Sign up to set email alerts
|

Optical Label-Free Nanoplasmonic Biosensing Using a Vertical-Cavity Surface-Emitting Laser and Charge-Coupled Device

Abstract: We present a compact platform for biochemosensing based on the combination of a vertical-cavity surface-emitting laser (VCSEL) light source, microelectromechanical systems (MEMS)-based microoptics, a specially designed nanoplasmonic sensing chip, and charge-coupled device (CCD) detector. The platform does not require any spectral analyzer for signal evaluation, showing good promise for facile integration, neither does it use any microscope setup for the signal collection or imaging. The analytical capabilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…By incorporating the nanoplasmonic chip in a flow cell, its biosensing capability was shown by preparing a biotinylated surface and subsequently monitoring the real-time binding of Neutravidin. Furthermore, also implementation of a Vertical-cavity surface-emitting laser (VCSEL)-optical excitation, combined with a CCD camera for detection, significantly reduces the dimensions of the setup [195]. In this work, the biosensing measurements based on the study of biotin-neutravidin interactions, showed similar outcome when compared to the use of a spectrophotometer.…”
Section: Integration Microfluidics and Multiplexingmentioning
confidence: 74%
“…By incorporating the nanoplasmonic chip in a flow cell, its biosensing capability was shown by preparing a biotinylated surface and subsequently monitoring the real-time binding of Neutravidin. Furthermore, also implementation of a Vertical-cavity surface-emitting laser (VCSEL)-optical excitation, combined with a CCD camera for detection, significantly reduces the dimensions of the setup [195]. In this work, the biosensing measurements based on the study of biotin-neutravidin interactions, showed similar outcome when compared to the use of a spectrophotometer.…”
Section: Integration Microfluidics and Multiplexingmentioning
confidence: 74%
“…The shift in the resonance position of the gold nanodome arrays in response to a change in the surrounding RI also leads to changes in extinction (or transmission) for each structure at wavelengths around the resonance maximum. Consequently, monitoring the plasmon shifts through the change in extinction at a single wavelength , is a promising method for reducing the size and cost of the required apparatus, as it eliminates the need for a spectrometer and broadband light source. , Figure a shows the change in extinction with wavelength for a sample (with P = 300 nm, H = 150 nm, and t = 40 nm) first immersed in ethanol and then in water. The differential spectra were used to highlight the wavelengths most sensitive to RI change.…”
Section: Resultsmentioning
confidence: 99%
“…The instrument does not require complex signal processing or microscopic optics for signal collection. The authors report low femtomoles detection levels of adsorbed proteins …”
Section: Microanalytical Systemsmentioning
confidence: 98%
“…The authors report low femtomoles detection levels of adsorbed proteins. 39 An array of electrodes fabricated on a monolithic quartz wafer was used to create a multichannel monolithic quartz crystal microbalance (MQCM) to miniaturize a MEMS device for highthroughput analysis. Applications for the device include classification and detection of volatile organic compounds (VOCs, i.e., ethanol, CH 2 Cl 2 , hexane) and water.…”
Section: Reviewmentioning
confidence: 99%